High prevalence of haemosporidian parasites in Eurasian jays - Schumm, Yvonne R.; Lederer-Ponzer, Naemi; Masello, Juan F.; Quillfeldt, Petra; Justus Liebig University Giessen (My University, 2024)
Avian haemosporidians are vector-borne parasites, infecting a great variety of birds. The order Passeriformes has the highest average infection probability; nevertheless, some common species of Passeriformes have been rather poorly studied. We investigated haemosporidians in one such species, the Eurasian jay Garrulus glandarius (Corvidae), from a forest population in Hesse, Central Germany. All individuals were infected with at least one haemosporidian genus (overall prevalence: 100%). The most common infection pattern was a mixed Haemoproteus and Leucocytozoon infection, whereas no Plasmodium infection was detected. Results on lineage diversity indicate a rather pronounced host-specificity of Haemoproteus and Leucocytozoon lineages infecting birds of the family Corvidae.
Keywords: ddc:570